Generalised design method for improving control quality of hybrid active power filter with injection circuit. Issue 5 (1st May 2014) - Nguyen, Trung Nhan; Luo, An; Shuai, Zhikang; Chau, Minh Thuyen; Li, Mingfei; Zhou, Leming
Abstract : Harmonic suppression is an important and challenging issue in electrical power systems and can be resolved by using hybrid active power filters with injection circuit (IHAPFs). In existing IHAPF systems, however, it is usually assumed that all parameters are determined accurately and unchanged over time, which is not true in real situations. It is well known that variations of system parameters may seriously degrade the performance of IHAPF systems. To obtain both efficiency and robustness, this study proposes a novel method for the generalised controller design of a three‐phase IHAPF system which can deal with deviations of system parameters. An optimum way to determine the stability bounds under various system parameters cases is introduced. The assessment of the stability bounds is based on the Routh criterion through solving the characteristic equation of the closed‐loop control system. Simulations and experimental results are presented to validate the correctness and effectiveness of the proposed design method for controller used in IHAPF system.